From Plant Oils to High‐Performance Supercapacitor Electrode: Poly(guaiazulene) via Photopolymerization - Ermis, Sena; Altinisik, Sinem; Catoglu, Fahri; Yagci, Yusuf; Sari, Erdem; Jockusch, Steffen; Koyuncu, Sermet; Kaya, Kerem (Wiley, 2024)
AbstractDue to the increasing global demand for electrical energy, the fabrication of advanced energy storage devices, such as supercapacitors (SCs), with outstanding performance is of paramount importance. Herein, the facile light‐induced synthesis of a conjugated conductive polymer, namely, poly(guaiazulene) (PGz) is reported on, using a naturally available, low‐cost monomer, guaiazulene (Gz). PGz and PGz_rGO (obtained by combining PGz with reduced graphene oxide (rGO)) exhibited high‐performance supercapacitor (SC) electrode properties, including remarkable specific capacitance (52.75 F g−1 at 0.24 A g−1 and 258.6 F g−1 at 5.00 A g−1, respectively), excellent cycling stability (97.1% and 94.0% stability after 5000 cycles), high power density (95.5 and 2118.8 W kg−1), and, most importantly, high energy density (5.81 and 30.57 Wh kg−1). These superior features are attributed to the hierarchical porous nature and high electrical/ionic conductivities of the photochemically obtained PGz. Contrary to previous techniques that require harsh reaction conditions, such as carbonization and coupling reactions, the reported photopolymerization involves solely the irradiation of an ethyl acetate solution of a Gz‐organic photoinitiator (2‐bromoacetophenone) mixture. The photochemical synthesis described here provides a powerful method to produce a sustainable and high‐performance SC electrode material, offering a great alternative to commercial SCs.
Keywords: poly(guaiazulene); Physics; QC1-999; photopolymerization; supercapacitor electrodes; conjugated conductive polymers polymers; Electric apparatus and materials. Electric circuits. Electric networks; hierarchical nanoporosity; TK452-454.4